Agricultural land market in Slovakia - economic and legal impacts of the Law No. 140/2014 Coll. on the land acquisition - Lazíková, Jarmila
Trh s poľnohospodárskou pôdou na Slovensku - ekonomické a právne dopady Zákona č. 140/2014 Zb. na získavanie pôdy.